Composition, negative electrode active material, method for producing negative electrode active material, and secondary battery

A composite resin of polysiloxane and phenol resin bonded with silicon nanoparticles enhances the discharge capacity maintenance rate of lithium-ion secondary batteries, addressing the limitations of existing silicon-based materials.

JP7619535B1Active Publication Date: 2025-01-22DIC CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024543180
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-04-28
Filing Date
2024-04-04
Publication Date
2025-01-22
Estimated Expiration
2044-04-04

AI Technical Summary

Technical Problem

The discharge capacity maintenance rate of lithium-ion secondary batteries using silicon-based negative electrode active materials is not adequately addressed in existing technologies, limiting their performance.

Method used

A composition containing silicon nanoparticles bonded with a composite resin formed by polysiloxane and phenol resin is used to produce a negative electrode active material, which is then fired to enhance the discharge capacity maintenance rate.

Benefits of technology

The use of a polysiloxane-phenol resin composite resin with silicon nanoparticles improves the discharge capacity maintenance rate of secondary batteries, achieving higher performance compared to traditional materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619535000015
    Figure 0007619535000015
  • Figure 0007619535000016
    Figure 0007619535000016
  • Figure 0007619535000017
    Figure 0007619535000017
Patent Text Reader

Abstract

The present invention relates to a composition, a negative electrode active material, a method for producing a negative electrode active material, and a secondary battery, and aims to provide a negative electrode active material capable of improving the retention rate of discharge capacity of a secondary battery, a composition for producing the negative electrode active material, and a method for producing the negative electrode active material. The present invention provides a composition containing silicon nanoparticles and a composite resin in which polysiloxane and a phenolic resin are bonded to each other. The composition is preferably used for producing a secondary battery material, and is particularly preferably used for producing a negative electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition, a negative electrode active material, a method for producing a negative electrode active material, and a secondary battery. [Background technology]

[0002] In recent years, the demand for small, high-capacity secondary batteries has increased with the spread of portable electronic devices such as smartphones. Among these, lithium-ion secondary batteries (sometimes written as LIB) have been rapidly deployed in electric vehicles (EVs), and the range of industrial use is continuing to expand. Carbon-based graphite negative electrode active materials (natural and artificial) are widely used as the negative electrode active material for lithium-ion secondary batteries, but the theoretical capacity density of graphite is low (372 mAh / g), and with the evolution of lithium-ion secondary batteries, the improvement of battery capacity is approaching its limit.

[0003] Silicon (Si) can form an alloy (intermetallic compound) with metallic lithium, making it possible to electrochemically store and release lithium ions. 22 When Si5 is formed, the theoretical capacity is 4200 mAh / g, and the silicon negative electrode active material can have a higher capacity than the graphite negative electrode active material.

[0004] For example, Patent Document 1 discloses a silicon active material produced by baking a composition obtained by mixing silicon nanoparticles, polysiloxane, and a phenol resin. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 7088438 Summary of the Invention [Problem to be solved by the invention]

[0006] According to the investigations of the present inventors, there is still room for further improvement in the negative electrode active material as described in Patent Document 1 in terms of the retention rate of the discharge capacity of a secondary battery.

[0007] Therefore, an object of one aspect of the present invention is to provide a negative electrode active material capable of improving the retention rate of the discharge capacity of a secondary battery, a composition for producing the negative electrode active material, and a method for producing the negative electrode active material. [Means for solving the problem]

[0008] The inventors have discovered that by firing a composition containing silicon nanoparticles and a composite resin in which polysiloxane and phenolic resin are pre-bonded, a negative electrode active material can be obtained that can improve the retention rate of the discharge capacity of a secondary battery, compared to the case where a composition obtained by mixing silicon nanoparticles, polysiloxane, and phenolic resin is fired.

[0009] The present invention includes the following aspects. [1] A composition containing silicon nanoparticles and a composite resin in which a polysiloxane and a phenolic resin are bonded to each other. [2] The composition according to [1], which is used for producing a secondary battery material. [3] The composition according to [1], which is used for producing a negative electrode active material. [4] A method for producing a negative electrode active material, comprising the step of firing a composition containing silicon nanoparticles and a composite resin in which a polysiloxane and a phenolic resin are bonded to each other. [5] A negative electrode active material comprising a fired product of a composition containing silicon nanoparticles and a composite resin in which a polysiloxane and a phenolic resin are bonded to each other. [6] A secondary battery comprising a negative electrode containing the negative electrode active material according to [5]. Effect of the Invention

[0010] According to one aspect of the present invention, it is possible to provide a negative electrode active material capable of improving the retention rate of the discharge capacity of a secondary battery, a composition for producing the negative electrode active material, and a method for producing the negative electrode active material. [Brief description of the drawings]

[0011] [Figure 1] 1 shows elemental mapping by SEM-EDX of the dried precursor mixture produced in Example 1. [Diagram 2] 1 shows elemental mapping by SEM-EDX of the dried precursor mixture produced in Example 2. [Diagram 3] 13 is elemental mapping by SEM-EDX of the dried precursor mixture produced in Example 3. [Figure 4] 13 is elemental mapping by SEM-EDX of the dried precursor mixture prepared in Example 4. [Diagram 5] 1 shows elemental mapping by SEM-EDX of the dried precursor mixture produced in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] One embodiment of the present invention is a composition containing silicon nanoparticles and a composite resin in which polysiloxane and phenolic resin are bonded to each other. The composition is preferably used for producing a secondary battery material, and is particularly preferably used for producing a negative electrode active material.

[0013] [Silicon nanoparticles] Silicon nanoparticles are particles made of silicon (Si, 0 valence). Silicon nanoparticles can be obtained, for example, by pulverizing silicon particles having a particle size of about several hundred μm to nano size.

[0014] The silicon particles can be pulverized using a pulverizer such as a ball mill, a bead mill, or a jet mill. The pulverization may be wet pulverization. The organic solvent used in the wet pulverization is not particularly limited as long as it is an organic solvent that can be suitably pulverized, and may be, for example, alcohol, ketone, or aromatic hydrocarbon such as toluene, xylene, naphthalene, or methylnaphthalene.

[0015] The average particle diameter (D50) of the silicon nanoparticles is preferably 10 nm or more, more preferably 20 nm or more, and even more preferably 30 nm or more, and is preferably 300 nm or less, more preferably 250 nm or less, and even more preferably 200 nm or less. When the average particle diameter is 10 nm or more, the aggregation of the silicon nanoparticles is suppressed, and the silicon nanoparticles can be easily uniformly dispersed in the negative electrode active material, and the increase of by-products on the surface when the silicon nanoparticles are baked can be suppressed. When the average particle diameter is 300 nm or less, the decrease in the charge / discharge performance of the negative electrode active material due to the pulverization phenomenon during charge / discharge can be suppressed.

[0016] The above-mentioned average particle diameter (D50) is the particle diameter at which the cumulative volume distribution curve of the silicon nanoparticles reaches 50% of the cumulative volume when the cumulative volume distribution curve is drawn from the small diameter side in the particle diameter distribution of the silicon nanoparticles. The average particle diameter (D50) is measured by a laser diffraction particle size distribution measuring device.

[0017] [Composite resin and its manufacturing method] A composite resin is a resin in which polysiloxane and phenol resin are bonded (chemically bonded) to each other. A composite resin is different from a mixture in which polysiloxane and phenol resin are simply mixed. The types of polysiloxane and phenol resin are not particularly limited. Below, an example of a method for compounding polysiloxane and phenol resin (a method for producing a composite resin) will be described, and then an example of the structure of the composite resin obtained by the method will be described.

[0018] In one embodiment, in the method for producing a composite resin, as described in detail below, a silane compound having an epoxy group and a hydrolyzable silyl group (hereinafter also referred to as an "epoxysilane compound") is used as a raw material for polysiloxane. Examples of such a production method include a production method (hereinafter also referred to as "production method A") in which a silane compound containing an epoxysilane compound is polycondensed in the presence of a phenolic resin to produce a polysiloxane, thereby obtaining a composite resin, a production method (hereinafter also referred to as "production method B") in which a phenolic resin is produced by polycondensing phenols and aldehydes in the presence of a polysiloxane that is a polycondensation product of a silane compound containing an epoxysilane compound, thereby obtaining a composite resin in which a polysiloxane and a phenolic resin are bonded to each other, and a production method (hereinafter also referred to as "production method C") in which a silane compound containing an epoxysilane compound is polycondensed all at once to obtain a composite resin in which a polysiloxane and a phenolic resin are bonded to each other.

[0019] In any of the manufacturing methods A to C for obtaining the above composite resin, it is preferable to use a silane compound in which an aromatic hydrocarbon group is bonded to a silicon atom as the silane compound for producing polysiloxane, from the viewpoint of making it easier to further improve the retention rate.

[0020] (Manufacturing method A) A method for producing a composite resin (production method A) according to one embodiment of the present invention includes a step (step (A-1)) of reacting a phenolic resin with a silane compound represented by the following formula (11) to obtain an intermediate. [ka] In the formula, R 11 represents a monovalent group having an epoxy group, R 12 and R 13 each independently represents an alkyl group, and m1 and m2 represent either (m1, m2)=(0, 3) or (1, 2).

[0021] The phenolic resin used in step (A-1) is not particularly limited. The phenolic resin can be obtained by reacting a phenol with an aldehyde by a known method. Alternatively, a commercially available phenolic resin may be used as the phenolic resin. In this specification, the term "phenolic" refers to a phenolic compound as a monomer constituting the phenolic resin, and does not include a phenolic resin.

[0022] Examples of phenolic resins include novolac-type phenolic resins (e.g., obtained by reacting phenols with aldehydes in the presence of an acid catalyst) and resol-type phenolic resins (e.g., obtained by reacting phenols with aldehydes in the presence of an alkali catalyst).

[0023] Examples of the phenols include monohydric phenols such as phenol, cresols such as o-cresol, m-cresol, and p-cresol; xylenols such as 2,3-xylenol, 2,4-xylenol, 2,5-xylenol, 2,6-xylenol, 3,4-xylenol, and 3,5-xylenol; ethylphenols such as o-ethylphenol, m-ethylphenol, and p-ethylphenol; butylphenols such as isopropylphenol, butylphenol, and p-tert-butylphenol; alkylphenols such as p-tert-amylphenol, p-octylphenol, p-nonylphenol, and p-cumylphenol; halogenated phenols such as fluorophenol, chlorophenol, bromophenol, and iodophenol; substituted monohydric phenols such as p-phenylphenol, aminophenol, nitrophenol, dinitrophenol, and trinitrophenol; and naphthols such as 1-naphthol and 2-naphthol. Examples of phenols include divalent or higher phenols such as resorcinol, alkylresorcin, pyrogallol, catechol, alkylcatechol, hydroquinone, alkylhydroquinone, phloroglucinol, and dihydroxynaphthalene. Examples of phenols include bisphenols such as bisphenol F and bisphenol A, and phenol derivatives derived from natural products such as cashew oil. These phenols may be used alone or in combination of two or more.

[0024] As the aldehydes, for example, formaldehyde such as formaldehyde, paraformaldehyde, trioxane, etc., acetaldehyde, furfural, etc. are effective, and urotropine (hexamethylenetetramine), etc. can be mentioned. These aldehydes may be used alone or in combination of two or more kinds.

[0025] The amount of the aldehydes may be 10 parts by mass or more, 20 parts by mass or more, or 25 parts by mass or more, and 50 parts by mass or less, 45 parts by mass or less, or 40 parts by mass or less, relative to 100 parts by mass of the phenols. The molar ratio of the amount of the aldehydes to the amount of the phenols (aldehydes / phenols) may be 0.3 or more, preferably 0.5 or more, and may be 3.0 or less, preferably 2.0 or less.

[0026] The phenol resin may be modified with a modifying agent such as melamine, acetoguanamine, benzoguanamine, cyanuric acid, a compound containing a triazine ring, such as methyl cyanurate, ethyl cyanurate, acetyl cyanurate, or cyanuric chloride; a urea-based compound, such as urea, ethylene urea, or thiourea; dicyandiamide; or guanidine.

[0027] By adding a catalyst such as an organic acid catalyst, an inorganic acid catalyst, or an alkaline catalyst as a reaction catalyst, polysiloxane, phenols, and aldehydes can be reacted. Examples of organic acid catalysts include formic acid, acetic acid, propionic acid, paratoluenesulfonic acid, methanesulfonic acid, lactic acid, mandelic acid, tartaric acid, citric acid, 2-hydroxybutyric acid, quinic acid, malic acid, paratoluenesulfonic acid, and phenolsulfonic acid. Examples of inorganic acid catalysts include boric acid, phosphoric acid, hydrochloric acid, and sulfuric acid. Examples of alkaline catalysts include ammonia, organic amines, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, choline, sodium hydroxide, potassium hydroxide, and calcium hydroxide.

[0028] R in Equation (11) 11 In one embodiment, may be a monovalent group having a glycidyl group, is preferably a monovalent group having a glycidoxy group, and is more preferably a group represented by the following formula (11a): [ka] In the formula, R arepresents an alkylene group, and * represents a bond bonded to the Si atom in formula (11).

[0029] R a The alkylene group represented by the formula (1) may be linear or branched. The number of carbon atoms in the alkylene group may be 1 or more, 2 or more, or 3 or more, and may be 10 or less, 9 or less, or 8 or less.

[0030] R in Equation (11) 11 In one embodiment, may be a monovalent group having an alicyclic epoxy group, and is preferably a group represented by the following formula (11b): [ka] In the formula, R b represents a single bond or an alkylene group, and * represents a bond bonded to the Si atom in formula (11).

[0031] R b The alkylene group represented by the formula (1) may be linear or branched. The number of carbon atoms in the alkylene group may be 1 or more, 2 or more, or 3 or more, and may be 10 or less, 9 or less, or 8 or less.

[0032] R 12 and R 13 The alkyl groups represented by the formula (I) may each independently be linear or branched. The number of carbon atoms in the alkyl groups may each independently be 1 or more, 5 or less, 4 or less, 3 or less, or 2 or less, or may be 1 or 2. 13 may be the same as each other or different from each other.

[0033] Specific examples of the silane compound represented by formula (11) include glycidoxypropyltrimethoxysilane, epoxycyclohexyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, and 8-glycidoxyoctyltrimethoxysilane.

[0034] The amount of the silane compound represented by formula (11) may be 1 part by mass or more or 3 parts by mass or more, and may be 1,500 parts by mass or less or 1,000 parts by mass or less, based on 100 parts by mass of the phenolic resin.

[0035] The amount of the silane compound represented by formula (11) may be 7 mol% or more and 62 mol% or less based on the total amount of the silane compound represented by formula (11) and the silane compound represented by formula (12) described later. The amount of the silane compound represented by formula (11) is preferably 10 to 60 mol% based on the total amount of the silane compound represented by formula (11) and the silane compound represented by formula (12) described later. The lower limit of the amount of the silane compound represented by formula (11) may be 12 mol%, 14 mol%, or 16 mol%. The upper limit of the amount of the silane compound represented by formula (11) may be 58 mol%, 56 mol%, or 54 mol%.

[0036] In step (A-1), a catalyst may be used when reacting the phenol resin with the silane compound represented by formula (11). Specific examples of the catalyst include imidazoles, organic phosphines, and tertiary amines. Examples of the imidazoles include 2-methylimidazole, 2-phenylimidazole, 2-phenyl-2-methylimidazole, and 2-heptadecylimidazole. Examples of the organic phosphines include tributylphosphine, methyldiphenylphosphine, triphenylphosphine, diphenylphosphine, and phenylphosphine. Examples of the tertiary amines include triethylenediamine, benzyldimethylamine, triethanolamine, dimethylaminoethyl, and tris(dimethylaminomethyl)phenol.

[0037] In step (A-1), in addition to the phenolic resin and the silane compound represented by formula (11), a silane compound other than the silane compound represented by formula (11) may be further reacted. As such a silane compound, a silane compound represented by formula (12) described in step (A-2) below can be used.

[0038] When a silane compound other than the silane compound represented by formula (11) is used, the amount of the silane compound may be 1 part by mass or more or 3 parts by mass or more, and may be 1,500 parts by mass or less or 1,000 parts by mass or less, relative to 100 parts by mass of the phenolic resin.

[0039] The reaction temperature and reaction time in step (A-1) can be appropriately set. The reaction temperature may be, for example, 70° C. or higher and 160° C. or lower. The reaction time may be, for example, 1 hour or higher and 5 hours or lower.

[0040] By the above-mentioned step (A-1), an intermediate is obtained which is a reaction product of the phenol resin and the silane compound represented by formula (11) (and further, a silane compound other than the silane compound represented by formula (11) used as necessary). More specifically, a hydroxyl group in the phenol resin and an epoxy group or an alkoxysilyl group in the silane compound represented by formula (11) (Si-OR in formula (11)) are reacted. 13 The hydroxyl group in the phenol resin may be a phenolic hydroxyl group (a hydroxyl group bonded to an aromatic ring in the phenol resin), and when the phenol resin has a methylol group, it may be a hydroxyl group constituting the methylol group.

[0041] Following the above-mentioned step (A-1), production method A includes a step (A-2) of polycondensing the intermediate obtained in the step (A-1) with a silane compound represented by the following formula (12). [ka] In the formula, R 21 represents an alkyl group, an aromatic hydrocarbon group, a vinyl group, or a (meth)acryloyloxyalkyl group; R 22 represents an alkyl group, and n1 and n2 represent either (n1, n2)=(1, 3) or (2, 2).

[0042] R 21The alkyl group represented by the formula (I) may be linear, branched, or cyclic. The number of carbon atoms in the alkyl group may be 1 or more, 6 or less, 5 or less, 4 or less, 3 or less, or 2 or less, or may be 1.

[0043] R 21 The aromatic hydrocarbon group represented by the formula (I) is a monovalent hydrocarbon group having an aromatic ring. Examples of the aromatic hydrocarbon group include an aryl group and an aralkyl group. Examples of the aryl group include a phenyl group, a tolyl group, a xylyl group, and a naphthyl group. Examples of the aralkyl group include a benzyl group and a phenethyl group. When n1 is 2, the two R 21 may be the same as or different from each other. From the viewpoint of further improving the retention rate, when (n1, n2)=(1, 3), R 21 is preferably an aromatic hydrocarbon group, and when (n1, n2)=(2, 2), R 21 At least one of these is preferably an aromatic hydrocarbon group.

[0044] R 21 The alkyl portion of the (meth)acryloyloxyalkyl group represented by the formula (I) may be linear or branched. The number of carbon atoms in the alkyl portion may be 1 or more, and may be 8 or less, 7 or less, 6 or less, 5 or less, 4 or less, or 3 or less.

[0045] R 22 The alkyl group represented by the formula (I) may be linear or branched. The number of carbon atoms in the alkyl group may be 1 or more, 4 or less, 3 or less, or 2 or less, or may be 1. 22 may be the same as each other or different from each other.

[0046] In step (A-2), one or more, preferably two or more, of the silane compounds represented by formula (12) are used. When two or more of the silane compounds represented by formula (12) are used, R 21is an alkyl group; or 21 It is preferable to use a combination of two or more silane compounds in which R is an aryl group.

[0047] Specific examples of the silane compound represented by formula (12) include silane compounds having an aromatic hydrocarbon group (R 21 R is an aromatic hydrocarbon group) silane compounds such as methyltrimethoxysilane, methyltriethoxysilane, methyltri-n-butoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, dimethyldi-n-butoxysilane, diethyldimethoxysilane, and methylcyclohexyldimethoxysilane. 21 Silane compounds in which all of R is an alkyl group, vinyltrimethoxysilane, divinyldimethoxysilane, and the like, 21 (R is a vinyl group), silane compounds having a (meth)acryloyloxyalkyl group such as 3-(meth)acryloyloxypropyltrimethoxysilane, 3-(meth)acryloyloxyoctyltrimethoxysilane, and 3-(meth)acryloyloxypropyltriethoxysilane, 21 and silane compounds in which the radical is a (meth)acryloyloxyalkyl group.

[0048] The amount of the silane compound represented by formula (12) may be 1 part by mass or more or 3 parts by mass or more, and may be 1,500 parts by mass or less or 1,000 parts by mass or less, based on 100 parts by mass of the phenol resin.

[0049] The amount of the silane compound represented by formula (12) may be 38 mol% or more and 93 mol% or less based on the total amount of the silane compound represented by formula (11) and the silane compound represented by formula (12). The amount of the silane compound represented by formula (12) is preferably 40 to 90 mol% based on the total amount of the silane compound represented by formula (11) and the silane compound represented by formula (12). The lower limit of the amount of the silane compound represented by formula (12) may be 52 mol%, 54 mol%, or 56 mol%. The upper limit of the amount of the silane compound represented by formula (12) may be 88 mol%, 86 mol%, or 84 mol%.

[0050] In step (A-2), a catalyst such as an organic acid catalyst, an inorganic acid catalyst, or an alkaline catalyst may be used to promote the reaction (hydrolysis condensation reaction) between the intermediate and the silane compound represented by formula (12). Examples of organic acid catalysts include formic acid, acetic acid, propionic acid, paratoluenesulfonic acid, methanesulfonic acid, lactic acid, mandelic acid, tartaric acid, citric acid, 2-hydroxybutyric acid, quinic acid, and malic acid. Examples of inorganic acid catalysts include boric acid and phosphoric acid. Examples of alkaline catalysts include ammonia, organic amines, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, choline, sodium hydroxide, potassium hydroxide, and calcium hydroxide.

[0051] In step (A-2), the intermediate and the silane compound represented by formula (12) may be reacted in one step or in multiple steps (e.g., two steps). For example, in the case of reacting in two steps, first, the intermediate and the silane compound represented by formula (12) R 21 is an aryl group, and then reacted with a silane compound represented by the formula (12) 21 It is possible to further react a silane compound in which the alkyl group is present.

[0052] The reaction temperature and reaction time in step (A-2) can be appropriately set. The reaction temperature may be, for example, 70° C. or higher and 120° C. or lower. The reaction time may be, for example, 1 hour or higher and 5 hours or lower.

[0053] The production method A may further include a step (A-3) of distilling the reaction product obtained in the step (A-2) under reduced pressure after the step (A-2). By the step (A-3), for example, methanol and water produced in the step (A-2) can be removed.

[0054] A composite resin in which polysiloxane and phenolic resin are bonded to each other can be obtained by the above-described manufacturing method A. The composite resin will be described in detail later.

[0055] (Manufacturing method B) A method for producing a composite resin (production method B) according to another embodiment of the present invention includes a step (step (B-1)) of polycondensing a phenol with an aldehyde in the presence of a polysiloxane having a structural unit represented by the following formula (21) and a structural unit represented by the following formula (22). [ka] In the formula, R 11 represents a monovalent group having an epoxy group, R 12 and R 13 each independently represents an alkyl group, p1 and p2 represent either (p1, p2)=(0, 1) or (1, 0), and * represents a bond. [ka] In the formula, R 21 represents an alkyl group, an aromatic hydrocarbon group, a vinyl group, or a (meth)acryloyloxyalkyl group; R 22 represents an alkyl group, q1 and q2 represent either (q1,q2)=(1,1) or (2,0), and * represents a bond. From the viewpoint of facilitating further improvement of the retention rate, when (q1,nq2)=(1,1), R 21is preferably an aromatic hydrocarbon group, and when (q1, q2)=(2, 0), R 21 At least one of these is preferably an aromatic hydrocarbon group.

[0056] R in Equation (21) 11 , R 12 and R 13 The details of R in formula (11) described in the above-mentioned production method A are 11 , R 12 and R 13 are the same as those in Eq. (22). 21 and R 22 The details of R in formula (21) described in the above-mentioned Production Method A are as follows: 21 and R 22 are the same as

[0057] A polysiloxane having a structural unit represented by formula (21) and a structural unit represented by formula (22) can be obtained by polycondensing a silane compound represented by formula (11) and a silane compound represented by formula (12) described in the above production method A by a known method.

[0058] The polysiloxane has one or more, preferably two or more, of the structural units represented by formula (22). When the polysiloxane has two or more of the structural units represented by formula (22), the polysiloxane preferably has R 21 is an alkyl group or R in formula (22) 21 is an aryl group.

[0059] The amount of the structural unit represented by formula (21) may be 7 mol% or more and 62 mol% or less based on the total amount of the structural unit represented by formula (21) and the structural unit represented by formula (22). The amount of the structural unit represented by formula (21) is preferably 10 to 60 mol% based on the total amount of the structural unit represented by formula (21) and the structural unit represented by formula (22). The lower limit of the amount of the structural unit represented by formula (21) may be 12 mol%, 14 mol%, or 16 mol%. The upper limit of the amount of the structural unit represented by formula (21) may be 58 mol%, 56 mol%, or 54 mol%.

[0060] The amount of the structural unit represented by formula (22) may be 38 mol% or more and 93 mol% or less based on the total amount of the structural unit represented by formula (21) and the structural unit represented by formula (22). The amount of the structural unit represented by formula (22) is preferably 60 to 90 mol% based on the total amount of the structural unit represented by formula (21) and the structural unit represented by formula (22). The lower limit of the amount of the structural unit represented by formula (22) may be 52 mol%, 54 mol%, or 56 mol%. The upper limit of the amount of the structural unit represented by formula (22) may be 88 mol%, 86 mol%, or 84 mol%.

[0061] In step (B-1), the polysiloxane is reacted with a phenol and an aldehyde to polycondense the phenol and the aldehyde. As the phenol and the aldehyde, one or more of the phenols and the aldehydes described in the above-mentioned production method A can be used.

[0062] The amount of polysiloxane may be 3 parts by mass or more, 5 parts by mass or more, or 10 parts by mass or more, and may be 4,500 parts by mass or less, 4,000 parts by mass or less, or 3,500 parts by mass or less, relative to 100 parts by mass of the phenols.

[0063] The amount of aldehydes may be 10 parts by mass or more, 20 parts by mass or more, or 25 parts by mass or more, and 50 parts by mass or less, 45 parts by mass or less, or 40 parts by mass or less, relative to 100 parts by mass of phenols. When the phenolic resin is a resol type phenolic resin, the molar ratio of the amount of aldehydes to the amount of phenols (aldehydes / phenols) may be 0.3 or more, preferably 0.5 or more, and may be 3.0 or less, preferably 2.0 or less.

[0064] In the step (B-1), examples of the modifying agent that may be used include compounds containing a triazine ring, such as melamine, acetoguanamine, benzoguanamine, cyanuric acid, methyl cyanurate, ethyl cyanurate, acetyl cyanurate, and cyanuric chloride; urea-based compounds, such as urea, ethylene urea, and thiourea; dicyandiamide; and guanidine.

[0065] In step (B-1), polysiloxane, phenols, and aldehydes can be reacted by adding a catalyst such as an organic acid catalyst, an inorganic acid catalyst, or an alkaline catalyst as a reaction catalyst. Examples of organic acid catalysts include formic acid, acetic acid, propionic acid, paratoluenesulfonic acid, methanesulfonic acid, lactic acid, mandelic acid, tartaric acid, citric acid, 2-hydroxybutyric acid, quinic acid, malic acid, paratoluenesulfonic acid, and phenolsulfonic acid. Examples of inorganic acid catalysts include boric acid, phosphoric acid, hydrochloric acid, and sulfuric acid. Examples of alkaline catalysts include ammonia, organic amines, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, choline, sodium hydroxide, potassium hydroxide, and calcium hydroxide.

[0066] The reaction temperature and reaction time in step (B-1) can be appropriately set. The reaction temperature may be, for example, 60° C. or higher and 180° C. or lower. The reaction time may be, for example, 1 hour or higher and 24 hours or lower.

[0067] The production method B may further include a step (B-2) of dehydrating the reaction product obtained in the step (B-1) under reduced pressure after the step (B-1). For example, the water generated in the step (B-1) can be removed by the step (B-2).

[0068] A composite resin in which polysiloxane and phenolic resin are bonded to each other can be obtained by the above-described manufacturing method B. The composite resin will be described in detail later.

[0069] (Manufacturing method C) A method for producing a composite resin (production method C) according to another embodiment of the present invention includes a step (step (C-1)) of polycondensing phenols, aldehydes, the silane compound represented by the above formula (11), and the silane compound represented by the above formula (12) all at once.

[0070] Details of the phenols, the silane compound represented by formula (11), and the silane compound represented by formula (12) used in step (C-1) are the same as those of the phenols, the silane compound represented by formula (11), and the silane compound represented by formula (12) described in production method A.

[0071] Details of the aldehydes are the same as those of the aldehydes described in the production method A. In this step (C-1), the phenols and the aldehydes are polycondensed to form a phenolic resin, the silane compound represented by formula (11) and the silane compound represented by formula (12) are polycondensed to form a polysiloxane, and further, the phenolic resin and the polysiloxane are bonded to each other to form a composite resin.

[0072] The amount of the silane compound represented by formula (11) may be 3 parts by mass or more, 5 parts by mass or more, or 10 parts by mass or more, and may be 3500 parts by mass or less, 3300 parts by mass or less, or 3100 parts by mass or less, relative to 100 parts by mass of the phenols.

[0073] The amount of the silane compound represented by formula (12) may be 3 parts by mass or more, 5 parts by mass or more, or 10 parts by mass or more, and may be 4,500 parts by mass or less, 4,000 parts by mass or less, or 3,500 parts by mass or less, relative to 100 parts by mass of the phenols.

[0074] The molar ratio of the amount of aldehydes to the amount of phenols (aldehydes / phenols) may be 0.3 or more, preferably 0.5 or more, and may be 3.0 or less, preferably 2.0 or less.

[0075] The amount of the silane compound represented by formula (11) may be 7 mol% or more and 62 mol% or less based on the total amount of the silane compound represented by formula (11) and the silane compound represented by formula (12) described later. The amount of the silane compound represented by formula (11) is preferably 10 to 60 mol% based on the total amount of the silane compound represented by formula (11) and the silane compound represented by formula (12) described later. The lower limit of the amount of the silane compound represented by formula (11) may be 12 mol%, 14 mol%, or 16 mol%. The upper limit of the amount of the silane compound represented by formula (11) may be 58 mol%, 56 mol%, or 54 mol%.

[0076] The amount of the silane compound represented by formula (12) may be 38 mol% or more and 93 mol% or less based on the total amount of the silane compound represented by formula (11) and the silane compound represented by formula (12). The amount of the silane compound represented by formula (12) is preferably 40 to 90 mol% based on the total amount of the silane compound represented by formula (11) and the silane compound represented by formula (12). The lower limit of the amount of the silane compound represented by formula (12) may be 52 mol%, 54 mol%, or 56 mol%. The upper limit of the amount of the silane compound represented by formula (12) may be 88 mol%, 86 mol%, or 84 mol%.

[0077] In the step (C-1), in order to promote the reaction (hydrolysis and condensation reaction), a catalyst (organic acid catalyst, inorganic acid catalyst, alkali catalyst, etc.) explained in the production method A may be used.

[0078] The reaction temperature and reaction time in step (C-1) can be appropriately set. The reaction temperature may be, for example, 60° C. or higher and 180° C. or lower. The reaction time may be, for example, 1 hour or higher and 24 hours or lower.

[0079] The production method C may further include, after the step (C-1), a step (C-2) of distilling the reaction product obtained in the step (C-1) under reduced pressure. By the step (C-2), for example, methanol and water produced in the step (C-1) can be removed.

[0080] A composite resin in which polysiloxane and phenolic resin are bonded to each other can be obtained by the above-described manufacturing method C. The composite resin will be described in detail later.

[0081] (Composite resin) In the composite resin obtained by each of the above-described manufacturing methods, the polysiloxane and the phenolic resin are bonded to each other. In this composite resin, the polysiloxane has a structural unit represented by the following formula (1A) or (1B) and a structural unit represented by the following formula (2). [ka] In the formula, R 11 represents a monovalent group having an epoxy group, R 12 represents an alkyl group, R 14 represents a linking group, R 15 represents a hydrogen atom or a hydrocarbon group, R 14 and R 15 may be bonded to each other to form a ring, p1 and p2 represent either (p1, p2)=(0, 1) or (1, 0), and * represents a bond. [ka] In the formula, R 21represents an alkyl group, an aromatic hydrocarbon group, a vinyl group, or a (meth)acryloyloxyalkyl group, q1 and q2 represent either (q1, q2)=(1, 1) or (2, 0), and * represents a bond.

[0082] R in formula (1A) 11 and R 12 The details of R in formula (11) described in the above-mentioned production method A are 11 and R 12 R in formula (1B) is the same as 12 The details of R in formula (11) described in the above-mentioned production method A are 12 It is the same as R in formula (2). 21 The details of R in formula (12) described in the above-mentioned Production Method A are as follows: 21 is the same as:

[0083] The phenolic resin is bonded to the polysiloxane via a hydroxyl group contained in the phenolic resin. The hydroxyl group in the phenolic resin may be a phenolic hydroxyl group (a hydroxyl group bonded to an aromatic ring in the phenolic resin), or, if the phenolic resin has a methylol group, may be a hydroxyl group constituting the methylol group.

[0084] In one embodiment, the phenolic resin may be bonded to the structural unit represented by formula (1A) or (1B) via a hydroxyl group, and the -(O-*) in the structural unit represented by formula (1A) p2 In the structural unit represented by formula (1B), -(O-*) p2 In the structural unit represented by formula (1B), -R 14 -CH(OH)-CH(R 15 In another embodiment, the phenol resin may be bonded to the structural unit represented by formula (2) via a hydroxyl group, and the -(O-*) in the structural unit represented by formula (2) may be bonded to the bond of the group represented by formula (2). q2 It may be bonded to a bond of a group represented by the following formula:

[0085] The structural unit represented by formula (1B) is a structural unit produced by reacting an epoxy group in the silane compound represented by formula (11) or a structural unit represented by formula (21) with a hydroxyl group in a phenol resin. 14 and R 15 is R in formula (11) and formula (21) 11 is a group having a structure corresponding to the structure of

[0086] For example, R in formula (11) and formula (21) 11 is a group represented by the above formula (11a), the structural unit represented by formula (1B) becomes a structural unit represented by the following formula (1C) (R 15 is a hydrogen atom). [ka] In the formula, R 12 , p1 and p2 are R in formula (1B) 12 , p1 and p2 are synonymous, and R a is R in formula (11a) a where * represents a bond.

[0087] For example, R in formula (11) and formula (21) 11 is a group represented by the above formula (11b), the structural unit represented by formula (1B) becomes a structural unit represented by the following formula (1D) (R 14 and R 15 are bonded to each other to form a ring). [ka] In the formula, R 12 , p1 and p2 are R in formula (1B) 12 , p1 and p2 are synonymous, and R b is R in formula (11b) b where * represents a bond.

[0088] In another embodiment, when the phenolic resin has an amino group, the phenolic resin may be bonded to the structural unit represented by formula (1B) via the amino group, and -R 14 -CH(OH)-CH(R 15 )-* may be bonded to a bond of the group represented by the formula (I).

[0089] In another embodiment, the polysiloxane has a vinyl group or a (meth)acryloyloxyalkyl group (R 21 is a vinyl group or a (meth)acryloyloxyalkyl group, the phenol resin may be bonded to the polysiloxane via the vinyl group or the (meth)acryloyloxyalkyl group.

[0090] The polysiloxane has one or more, preferably two or more, of the structural units represented by formula (2). When the polysiloxane has two or more of the structural units represented by formula (2), the polysiloxane preferably has R 21 is an alkyl group or R in formula (22) 21 is an aryl group.

[0091] The amount of the structural unit represented by formula (1A) or (1B) may be 7 mol% or more and 62 mol% or less based on the total amount of the structural unit represented by formula (1A) or (1B) and the structural unit represented by formula (2). The amount of the structural unit represented by formula (1A) or (1B) is preferably 10 to 60 mol% based on the total amount of the structural unit represented by formula (1A) or (1B) and the structural unit represented by formula (2). The lower limit of the amount of the structural unit represented by formula (1A) or (1B) may be 12 mol%, 14 mol%, or 16 mol%. The upper limit of the amount of the structural unit represented by formula (1A) or (1B) may be 58 mol%, 56 mol%, or 54 mol%.

[0092] The amount of the structural unit represented by formula (2) may be 38 mol% or more and 93 mol% or less based on the total amount of the structural unit represented by formula (1A) or (1B) and the structural unit represented by formula (2). The amount of the structural unit represented by formula (2) is preferably 40 to 90 mol% based on the total amount of the structural unit represented by formula (1A) or (1B) and the structural unit represented by formula (2). The lower limit of the amount of the structural unit represented by formula (2) may be 52 mol%, 54 mol%, or 56 mol%. The upper limit of the amount of the structural unit represented by formula (2) may be 88 mol%, 86 mol%, or 84 mol%.

[0093] In the composite resin, the mass ratio (polysiloxane segment / phenol resin segment) of the content of the structure derived from polysiloxane (polysiloxane segment) to the content of the structure derived from the phenol resin (phenol resin segment) may be 5 / 95 or more, 10 / 90 or more, or 15 / 85 or more, and may be 95 / 5 or less, 90 / 10 or less, 80 / 20 or less, or 70 / 30 or less.

[0094] The content of the composite resin in the composition is preferably 50 parts by mass or more, more preferably 100 parts by mass or more, and even more preferably 150 parts by mass or more, relative to 100 parts by mass of silicon nanoparticles, from the viewpoint of further improving the retention rate of the discharge capacity of the secondary battery, and is preferably 500 parts by mass or less, more preferably 400 parts by mass or less, and even more preferably 350 parts by mass or less, from the viewpoint of further improving the initial efficiency of the secondary battery. When the composition further contains a dispersant, the content of the composite resin in the composition may be the above content relative to 100 parts by mass of the total amount of the silicon nanoparticles and the dispersant.

[0095] The composition may contain only silicon nanoparticles and a composite resin, or may contain other components in addition to the silicon nanoparticles and the composite resin.

[0096] Other components include, for example, a dispersion medium and a dispersant. The dispersion medium may be, for example, an organic solvent such as methyl ethyl ketone. The dispersant may be a known dispersant capable of improving the dispersibility of silicon nanoparticles in the dispersion medium. Examples of dispersants include non-aqueous dispersants. Examples of non-aqueous dispersants include polymer-type (polyether-based, polyalkylene polyamine-based, polycarboxylic acid partial alkyl ester-based, etc.), low molecular-weight type (polyhydric alcohol ester-based, alkyl polyamine-based, etc.), inorganic polyphosphate-based, etc.

[0097] The content of the dispersion medium may be, for example, 200 parts by mass or more and 600 parts by mass or less relative to 100 parts by mass of silicon nanoparticles. The content of the dispersant is preferably 7 parts by mass or more, more preferably 12 parts by mass or more, and preferably 75 parts by mass or less, more preferably 50 parts by mass or less relative to 100 parts by mass of silicon nanoparticles, from the viewpoint of suitably dispersing the silicon nanoparticles in the dispersion medium.

[0098] [Negative electrode active material and its manufacturing method] Next, a method for producing a negative electrode active material using the above composition will be described. One embodiment of the present invention includes a step of baking a composition containing silicon nanoparticles and a composite resin in which polysiloxane and a phenolic resin are bonded to each other (baking step).

[0099] The composition used in the baking step may be in the form of a negative electrode active material precursor in which silicon nanoparticles and a composite resin are uniformly mixed. The negative electrode active material precursor is prepared by, for example, mixing a dispersion of silicon nanoparticles with a composite resin, removing the solvent, and drying to homogenize (homogenization step). That is, the method for producing a negative electrode active material according to one embodiment may further include a homogenization step before the baking step. The dispersion of silicon nanoparticles may contain the above-mentioned dispersion medium and dispersant in addition to silicon nanoparticles.

[0100] The mixing ratio of the silicon nanoparticle dispersion and the composite resin in the homogenization process may be, for example, 100 to 400 parts by mass, 150 to 380 parts by mass, or 170 to 360 parts by mass of the composite resin per 100 parts by mass of silicon nanoparticles (solid content).

[0101] The solvent removal in the homogenization step can be carried out under an inert gas (such as nitrogen gas) flow at, for example, 80 to 150° C. The drying in the homogenization step can be, for example, reduced pressure drying at 25 to 200° C. The drying time can be, for example, 1 minute to 24 hours.

[0102] The negative electrode active material precursor obtained in the homogenization step may contain C, N, O, and Si as constituent elements. The ratio of C in the negative electrode active material precursor may be 35 parts by mass or more, 40 parts by mass or more, or 45 parts by mass or more, and 70 parts by mass or less, 65 parts by mass or less, or 60 parts by mass or less, relative to 100 parts by mass of the total of C, N, O, and Si. The ratio of N in the negative electrode active material precursor may be 1 part by mass or more, 2 parts by mass or more, or 3 parts by mass or more, and 7 parts by mass or less, 6 parts by mass or less, or 5 parts by mass or less, relative to 100 parts by mass of the total of C, N, O, and Si. The ratio of O in the negative electrode active material precursor may be 5 parts by mass or more, 7 parts by mass or more, or 9 parts by mass or more, and 30 parts by mass or less, 25 parts by mass or less, or 20 parts by mass or less, relative to 100 parts by mass of the total of C, N, O, and Si. The ratio of Si in the negative electrode active material precursor may be 10 parts by mass or more, 13 parts by mass or more, or 15 parts by mass or more, and may be 50 parts by mass or less, 45 parts by mass or less, or 40 parts by mass or less, relative to 100 parts by mass of the total of C, N, O, and Si.

[0103] In the calcination step, the composition (negative electrode active material precursor) is calcined in an inert atmosphere (e.g., nitrogen atmosphere) at a maximum temperature of 1000°C to 1180°C for 1 to 48 hours. The calcination method is not particularly limited, and may be a continuous method, a batch method, or the like, using a device having a heating function in an inert atmosphere. The device may be appropriately selected from a fluidized bed reactor, a rotary furnace, a vertical moving bed reactor, a tunnel furnace, a batch furnace, a rotary kiln, or the like depending on the purpose.

[0104] The method for producing a negative electrode active material according to an embodiment may further include a step of pulverizing the fired product obtained in the firing step (pulverization step). The pulverization may be performed in one step until the fired product has a desired particle size, or may be performed in multiple steps. The pulverization method may be appropriately selected depending on the size of the fired product, and may be pulverization using a jaw crusher, roll crusher, glow mill, ball mill, bead mill, jet mill, or the like.

[0105] The negative electrode active material can be obtained by the manufacturing method described above. That is, one embodiment of the present invention is a negative electrode active material containing a sintered product of a composition containing silicon nanoparticles and a composite resin in which polysiloxane and a phenol resin are bonded to each other.

[0106] [Anode and secondary battery] The above-mentioned negative electrode active material is suitably used for a negative electrode (a negative electrode of a secondary battery). That is, one embodiment of the present invention is a negative electrode containing the above-mentioned negative electrode active material. Another embodiment of the present invention is a secondary battery including a negative electrode containing the above-mentioned negative electrode active material.

[0107] The negative electrode includes, for example, a current collector and a negative electrode material layer provided on the current collector. The current collector may be, for example, a metal foil such as copper, nickel, titanium, stainless steel, etc. The negative electrode material layer includes, for example, the above-mentioned negative electrode active material and an organic binder.

[0108] The organic binder is not particularly limited, but examples thereof include styrene-butadiene rubber copolymers (SBR); ethylenically unsaturated carboxylic acid esters (e.g., methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, (meth)acrylonitrile, and hydroxyethyl)polyvinylidene fluoride, polyethylene oxide, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polyimide, polyamideimide, and polymer compounds such as carboxymethylcellulose (CMC).

[0109] The content of the negative electrode active material in the negative electrode layer may be 70% by mass or more, 80% by mass or more, or 85% by mass or more, and may be 99% by mass or less, 98% by mass or less, or 97% by mass or less. The content of the organic binder in the negative electrode layer may be 1% by mass or more, 2% by mass or more, or 3% by mass or more, and may be 30% by mass or less, 20% by mass or less, or 15% by mass or less.

[0110] The negative electrode layer may further contain a conductive assistant. Examples of the conductive assistant include carbon black, graphite, acetylene black, oxides and nitrides that exhibit electrical conductivity, etc. The content of the conductive assistant may be 1 part by mass or more and 15 parts by mass or less with respect to 100 parts by mass of the negative electrode active material.

[0111] The secondary battery including the negative electrode may be a non-aqueous electrolyte secondary battery or a solid electrolyte secondary battery, and is preferably a non-aqueous electrolyte secondary battery. The non-aqueous electrolyte secondary battery includes, for example, the negative electrode, a positive electrode, a separator, and an electrolyte solution.

[0112] The negative electrode includes, for example, a current collector and a positive electrode layer provided on the current collector. The current collector may be, for example, a metal foil such as copper, nickel, titanium, or stainless steel.

[0113] The positive electrode material contained in the positive electrode layer may be, for example, a metal compound, a metal oxide, a metal sulfide, or a conductive polymer material capable of doping or intercalating lithium ions. Specific examples include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), and composite oxides thereof (LiCoO2, LiNiO2, LiMn ... x Ni y Mn z O2, x+y+z=1), lithium manganese spinel (LiMn2O4), lithium vanadium compounds, V2O5, V6O 13 , VO2, MnO2, TiO2, MoV2O8, TiS2, V2S5, VS2, MoS2, MoS3, Cr3O8, Cr2O5, olivine-type LiMPO4 (M: Co, Ni, Mn, Fe), conductive polymers such as polyacetylene, polyaniline, polypyrrole, polythiophene, polyacene, porous carbon, etc. can be used alone or in combination.

[0114] As the separator, for example, a nonwoven fabric, a cloth, a microporous film, or a combination thereof, mainly composed of a polyolefin such as polyethylene or polypropylene can be used. If the positive electrode and the negative electrode of the nonaqueous electrolyte secondary battery to be produced are not in direct contact with each other, there is no need to use a separator.

[0115] As the electrolyte, for example, a so-called organic electrolyte can be used in which a lithium salt such as LiClO4, LiPF6, LiAsF6, LiBF4, or LiSO3CF3 is dissolved in a non-aqueous solvent such as ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, fluoroethylene carbonate, cyclopentanone, sulfolane, 3-methylsulfolane, 2,4-dimethylsulfolane, 3-methyl-1,3-oxazolidin-2-one, γ-butyrolactone, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, butyl methyl carbonate, ethyl propyl carbonate, butyl ethyl carbonate, dipropyl carbonate, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, methyl acetate, or ethyl acetate, or a mixture of two or more components.

[0116] The structure of the non-aqueous electrolyte secondary battery is not particularly limited, but typically, a positive electrode, a negative electrode, and a separator, if necessary, are wound into a flat spiral shape to form a wound electrode plate group, or these are stacked in a flat plate shape to form a stacked electrode plate group, and the electrode plate group is sealed in an exterior body. Non-aqueous electrolyte secondary batteries are used as paper batteries, button batteries, coin batteries, stacked batteries, cylindrical batteries, square batteries, etc. EXAMPLES

[0117] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these.

[0118] Synthesis Example 1: Preparation of Silicon Nanoparticle Dispersion A1 (Silicon Nanoparticle Dispersion Process) In a 150 ml container of a small bead mill device, zirconia beads with a particle size of 0.1 mm to 0.2 mm at a filling rate of 60% and 165 parts by mass of methyl ethyl ketone solvent (MEK) were placed. Then, 40 parts by mass of silicon powder ("SIE23PB" manufactured by Kojundo Chemical Co., Ltd.) with an average particle size of 5 μm and 8 parts by mass of cationic dispersant liquid ("BYK102" manufactured by BYK Japan Co., Ltd.) were placed, and wet grinding was performed using a bead mill to obtain a dispersion A1 of silicon nanoparticles in the form of a dark brown liquid with a solid concentration of 23% by mass. The average particle size (D50) of the silicon nanoparticles was 85 nm.

[0119] Synthesis Example 2: Preparation of Silicon Nanoparticle Dispersion A2 (Silicon Nanoparticle Dispersion Process) In a 150 ml container of a small bead mill device, zirconia beads with a particle size of 0.1 mm to 0.2 mm at a filling rate of 60% and 193 parts by mass of methyl ethyl ketone solvent (MEK) were placed. Then, 40 parts by mass of silicon powder ("SIE23PB" manufactured by Kojundo Chemical Co., Ltd.) with an average particle size of 5 μm and 16 parts by mass of cationic dispersant liquid ("BYK102" manufactured by BYK Japan Co., Ltd.) were placed, and wet grinding was performed using a bead mill to obtain a dispersion A2 of silicon nanoparticles in the form of a dark brown liquid with a solid concentration of 23% by mass. The average particle size (D50) of the silicon nanoparticles was 83 nm.

[0120] Synthesis Example 3: Preparation of Composite Resin B1 A reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube and a nitrogen gas inlet was charged with 100 parts by mass of MEK, 469 parts by mass of glycidoxypropyltrimethoxysilane (GPTMS), and 275 parts by mass of dimethyldimethoxysilane (DMDMS), and the temperature was raised to 75 ° C. while stirring, and a mixture of 1 part by mass of butyl acid phosphate and 160 parts by mass of deionized water was dropped over 1 hour. Then, 163 parts by mass of methyltrimethoxysilane (MTMS) was added, and the mixture was stirred at the same temperature for 4 hours to cause a hydrolysis condensation reaction, thereby obtaining a reaction product. Next, the reaction product was distilled for 10 hours under a reduced pressure of 10 to 300 kPa at a temperature of 60 to 80 ° C. to remove the produced methanol and water, and then 430 parts by mass of MEK was added to obtain 1,000 parts by mass of a solution of polysiloxane b1 having a non-volatile content of 60.0% by mass.

[0121] Next, 350 parts by mass of the polysiloxane b1, 234 parts by mass of phenol, 234 parts by mass of 2-naphthol, 16 parts by mass of melamine, 344 parts by mass of 50% formalin, and 15.4 parts by mass of 25% aqueous ammonia were charged into a reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube, and a nitrogen gas inlet, and the mixture was heated to 80° C. with stirring, and reacted at 80° C. for 2 hours. Next, dehydration was performed under reduced pressure of 10 to 300 kPa, and 380 parts by mass of MEK was added to obtain 1,000 parts by mass of a solution of composite resin B1 with a non-volatile content of 60.0% by mass.

[0122] In the obtained composite resin B1, the content of the epoxysilane compound in the total amount of the silane compound (hereinafter referred to as "epoxysilane content") was 37.5 mol%, and the mass ratio of the content of the polysiloxane segment to the content of the phenol resin segment (hereinafter referred to as "PSi / Ph") was 30 / 70. In addition, the decomposition starting temperature of the composite resin B1 measured by the method described later was 248°C.

[0123] Synthesis Example 4: Preparation of Composite Resin B2 The same synthesis operation as for the composite resin B1 was carried out, except that the amount of the polysiloxane b1 added after obtaining the polysiloxane b1 was changed to 535 parts by mass, to obtain 1,000 parts by mass of a solution of the composite resin B2. In the obtained composite resin B2, the content of epoxysilane was 37.5 mol%, and PSi / Ph was 40 / 60. In addition, the decomposition start temperature of the composite resin B2 measured by the method described below was 238°C.

[0124] Synthesis Example 5: Preparation of Composite Resin B3 The amount of the polysiloxane b1 obtained was 213 parts by mass, 496 parts by mass of 3,5-xylenol, 16 parts by mass of melamine, 292 parts by mass of 50% formalin, and 9.9 parts by mass of 25% aqueous ammonia. The mixture was heated to 80°C while stirring, and reacted at 80°C for 2 hours. Next, dehydration was performed under reduced pressure of 10 to 300 kPa, and 410 parts by mass of MEK was added to obtain 1,000 parts by mass of a solution of composite resin B3 having a non-volatile content of 60.0% by mass. In the obtained composite resin B3, the content of epoxysilane was 37.5 mol%, and PSi / Ph was 20 / 80. The decomposition start temperature of composite resin B3 measured by the method described below was 310°C.

[0125] Synthesis Example 6: Preparation of Composite Resin B4 A reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube and a nitrogen gas inlet was charged with 180 parts by mass of MEK, 290 parts by mass of GPTMS, 374 parts by mass of DMDMS and 277 parts by mass of MTMS, and then the temperature in the system was raised to 70°C while stirring, and a mixture of 5 parts by mass of triethylamine (TEA) and 200 parts by mass of deionized water was dropped over 2 hours. Then, the mixture was stirred at the same temperature for 6 hours to cause a hydrolysis condensation reaction, and a reaction product was obtained. Next, the reaction product was distilled for 10 hours under a reduced pressure of 10 to 300 kPa at 60 to 80°C to remove the produced methanol and water, and then 350 parts by mass of MEK was added to obtain 1,000 parts by mass of a solution of polysiloxane b2 having a non-volatile content of 60.0% by mass.

[0126] Next, 213 parts by mass of the polysiloxane b2, 496 parts by mass of 3,5-xylenol, 16 parts by mass of melamine, 292 parts by mass of 50% formalin, and 9.9 parts by mass of 25% aqueous ammonia were charged into a reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube, and a nitrogen gas inlet, and the temperature was raised to 80° C. with stirring, and the mixture was reacted at 80° C. for 2 hours. Next, dehydration was performed under reduced pressure of 10 to 300 kPa, and 410 parts by mass of MEK was added to obtain 1,000 parts by mass of a solution of composite resin B4 having a non-volatile content of 60.0% by mass.

[0127] In the obtained composite resin B4, the content of epoxysilane was 20 mol %, and PSi / Ph was 20 / 80. In addition, the decomposition starting temperature of the composite resin B4 measured by the method described later was 301°C.

[0128] Synthesis Example 7: Preparation of Polysiloxane C A reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube, and a nitrogen gas inlet was charged with 1,421 parts by mass of MTMS and heated to 60° C. Next, a mixture of 0.17 parts by mass of butyl acid phosphate and 207 parts by mass of deionized water was dropped into the reaction vessel over 5 minutes, and the mixture was stirred at a temperature of 80° C. for 4 hours to carry out a hydrolysis and condensation reaction of MTMS.

[0129] The condensate obtained by the hydrolysis and condensation reaction was distilled at a temperature of 40°C to 60°C and under a reduced pressure of 40 kPa to 1.3 kPa. Note that "under a reduced pressure of 40 kPa to 1.3 kPa" means that the reduced pressure condition at the start of methanol distillation was 40 kPa, and the pressure was finally reduced to 1.3 kPa. By removing the methanol and water produced during the reaction, 1,000 parts by mass of a liquid containing a condensate (c1) of MTMS having a number average molecular weight of 1,000 to 5,000 was obtained. The active ingredient of the obtained liquid was 70% by mass.

[0130] The above-mentioned effective ingredient is calculated by dividing the theoretical yield (parts by mass) when all the methoxy groups of a silane monomer such as MTMS undergo a condensation reaction by the actual yield (parts by mass) after the condensation reaction, i.e. [theoretical yield (parts by mass) when all the methoxy groups of a silane monomer undergo a condensation reaction / actual yield (parts by mass)].

[0131] Next, 150 parts by mass of MEK, 105 parts by mass of MTMS, and 277 parts by mass of DMDMS were placed in a reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube, and a nitrogen gas inlet, and the temperature was raised to 80°C.

[0132] Next, at the same temperature, a mixture containing 21 parts by mass of methyl methacrylate, 4 parts by mass of butyl methacrylate, 3 parts by mass of butyric acid, 2 parts by mass of methacryloyloxypropyltrimethoxysilane, 3 parts by mass of MEK, and 0.6 parts by mass of butylperoxy-2-ethylhexanoate was dropped into the reaction vessel over 6 hours. After the dropwise addition was completed, the mixture was further reacted at the same temperature for 20 hours to obtain an organic solvent solution of a vinyl polymer (c2) having a hydrolyzable silyl group and a number average molecular weight of 10,000.

[0133] Next, a mixture of 0.04 parts by mass of butyl acid phosphate and 112 parts by mass of deionized water was added dropwise over a period of 5 minutes, and the mixture was stirred at the same temperature for a further 10 hours to cause a hydrolysis condensation reaction, thereby obtaining a liquid containing a resin in which the hydrolyzable silyl group of the vinyl polymer (c2) and the hydrolyzable silyl group and silanol group of the polysiloxane derived from MTMS and DMDMS were bonded together.

[0134] Next, 472 parts by mass of the MTMS condensate (c1) and 80 parts by mass of deionized water were added to this liquid, and the mixture was stirred at the same temperature for 10 hours to cause a hydrolysis condensation reaction, and the produced methanol and water were removed by distillation under the same conditions as in Synthesis Example 2. Next, 250 parts by mass of MEK was added to obtain 1000 parts by mass of a solution of polysiloxane C with a non-volatile content of 60.1% by mass. The decomposition onset temperature of polysiloxane C measured by the method described below was 421°C.

[0135] Synthesis Example 8: Preparation of Composite Resin B5 A reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube and a nitrogen gas inlet was charged with 100 parts by mass of MEK, 665 parts by mass of GPTMS, 80 parts by mass of DMDMS, and 90 parts by mass of phenyltrimethoxysilane (PTMS), and then the temperature in the system was raised to 70 ° C. while stirring, and a mixture of 1 part by mass of butyl acid phosphate and 160 parts by mass of deionized water was dropped over 1 hour. Then, 65 parts by mass of MTMS was added, and the mixture was stirred at the same temperature for 4 hours to cause a hydrolysis condensation reaction, and a reaction product was obtained. Next, the reaction product was distilled for 10 hours under a reduced pressure of 10 to 300 kPa at 60 to 80 ° C. to remove the produced methanol and water, and then 430 parts by mass of MEK was added to obtain 1,000 parts by mass of a solution of polysiloxane b3 having a non-volatile content of 60.0% by mass.

[0136] Next, 350 parts by mass of the polysiloxane b3, 234 parts by mass of phenol, 234 parts by mass of 2-naphthol, 16 parts by mass of melamine, 344 parts by mass of 50% formalin, and 15.4 parts by mass of 25% aqueous ammonia were charged into a reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube, and a nitrogen gas inlet, and the mixture was heated to 80° C. with stirring, and reacted at 80° C. for 2 hours. Next, dehydration was performed under reduced pressure of 10 to 300 kPa, and 380 parts by mass of MEK was added to obtain 1,000 parts by mass of a solution of composite resin B5 having a non-volatile content of 60.0% by mass.

[0137] In the obtained composite resin B5, the epoxysilane content was 65 mol %, the phenyltrimethoxysilane content was 10 mol %, and PSi / Ph was 30 / 70.

[0138] Synthesis Example 9: Preparation of Composite Resin B6 A reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube and a nitrogen gas inlet was charged with 100 parts by mass of MEK, 341 parts by mass of GPTMS, 116 parts by mass of DMDMS and 301 parts by mass of PTMS, and then the temperature in the system was raised to 70 ° C. while stirring, and a mixture of 1 part by mass of butyl acid phosphate and 160 parts by mass of deionized water was dropped over 1 hour. Then, 145 parts by mass of MTMS was added and stirred at the same temperature for 4 hours to cause a hydrolysis condensation reaction, thereby obtaining a reaction product. Next, the reaction product was distilled for 10 hours under a reduced pressure of 10 to 300 kPa at 60 to 80 ° C. to remove the produced methanol and water, and then 430 parts by mass of MEK was added to obtain 1,000 parts by mass of a solution of polysiloxane b4 having a non-volatile content of 60.0% by mass.

[0139] Next, 350 parts by mass of the polysiloxane b4, 234 parts by mass of phenol, 234 parts by mass of 2-naphthol, 344 parts by mass of 50% formalin, and 15.4 parts by mass of 25% aqueous ammonia were charged into a reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube, and a nitrogen gas inlet, and the temperature was raised to 80° C. with stirring, and the mixture was reacted at 80° C. for 2 hours. Next, dehydration was performed under reduced pressure of 10 to 300 kPa, and 380 parts by mass of MEK was added to obtain 1,000 parts by mass of a solution of composite resin B6 having a non-volatile content of 60.0% by mass.

[0140] In the obtained composite resin B6, the epoxysilane content was 30 mol %, the phenyltrimethoxysilane content was 30 mol %, and PSi / Ph was 30 / 70.

[0141] Synthesis Example 10: Preparation of Composite Resin B7 A reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube and a nitrogen gas inlet was charged with 100 parts by mass of MEK, 140 parts by mass of GPTMS, 100 parts by mass of DMDMS and 515 parts by mass of PTMS, and then the temperature in the system was raised to 70 ° C. while stirring, and a mixture of 1 part by mass of butyl acid phosphate and 160 parts by mass of deionized water was dropped over 1 hour. Then, 155 parts by mass of MTMS was added and stirred at the same temperature for 4 hours to cause a hydrolysis condensation reaction, thereby obtaining a reaction product. Next, the reaction product was distilled for 10 hours under a reduced pressure of 10 to 300 kPa at 60 to 80 ° C. to remove the produced methanol and water, and then 430 parts by mass of MEK was added to obtain 1,000 parts by mass of a solution of polysiloxane b5 having a non-volatile content of 60.0% by mass.

[0142] Next, 350 parts by mass of the polysiloxane b5, 234 parts by mass of phenol, 234 parts by mass of 2-naphthol, 16 parts by mass of melamine, 344 parts by mass of 50% formalin, and 15.4 parts by mass of 25% aqueous ammonia were charged into a reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube, and a nitrogen gas inlet, and the temperature was raised to 80° C. while stirring, and the mixture was reacted at 80° C. for 2 hours. Next, dehydration was performed under reduced pressure of 10 to 300 kPa, and 380 parts by mass of MEK was added to obtain 1,000 parts by mass of a solution of composite resin B7 having a non-volatile content of 60.0% by mass.

[0143] In the obtained composite resin B7, the epoxysilane content was 12 mol %, the phenyltrimethoxysilane content was 50 mol %, and PSi / Ph was 30 / 70.

[0144] Synthesis Example 11: Preparation of Composite Resin B8 A reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube and a nitrogen gas inlet was charged with 100 parts by mass of MEK, 105 parts by mass of GPTMS, 39 parts by mass of DMDMS and 740 parts by mass of PTMS, and then the temperature in the system was raised to 70 ° C. while stirring, and a mixture of 1 part by mass of butyl acid phosphate and 160 parts by mass of deionized water was dropped over 1 hour. Then, 19 parts by mass of MTMS was added and stirred at the same temperature for 4 hours to cause a hydrolysis condensation reaction, thereby obtaining a reaction product. Next, the reaction product was distilled for 10 hours under a reduced pressure of 10 to 300 kPa at 60 to 80 ° C. to remove the produced methanol and water, and then 430 parts by mass of MEK was added to obtain 1,000 parts by mass of a solution of polysiloxane b6 having a non-volatile content of 60.0% by mass.

[0145] Next, 350 parts by mass of the polysiloxane b6, 234 parts by mass of phenol, 234 parts by mass of 2-naphthol, 16 parts by mass of melamine, 344 parts by mass of 50% formalin, and 15.4 parts by mass of 25% aqueous ammonia were charged into a reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube, and a nitrogen gas inlet, and the temperature was raised to 80° C. while stirring, and the mixture was reacted at 80° C. for 2 hours. Next, dehydration was performed under reduced pressure of 10 to 300 kPa, and 380 parts by mass of MEK was added to obtain 1,000 parts by mass of a solution of composite resin B8 having a non-volatile content of 60.0% by mass.

[0146] In the obtained composite resin B8, the epoxysilane content was 10 mol %, the phenyltrimethoxysilane content was 80 mol %, and PSi / Ph was 30 / 70.

[0147] Synthesis Example 12: Preparation of Composite Resin B9 A reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube and a nitrogen gas inlet was charged with 100 parts by mass of MEK, 52 parts by mass of GPTMS, 16 parts by mass of DMDMS and 825 parts by mass of PTMS, and then the temperature in the system was raised to 70°C while stirring, and a mixture of 1 part by mass of butyl acid phosphate and 160 parts by mass of deionized water was dropped over 1 hour. Then, 13 parts by mass of MTMS was added and stirred at the same temperature for 4 hours to carry out a hydrolysis condensation reaction, thereby obtaining a reaction product. Next, the reaction product was distilled for 10 hours under a reduced pressure of 10 to 300 kPa at 60 to 80°C to remove the produced methanol and water, and then 430 parts by mass of MEK was added to obtain 1,000 parts by mass of a solution of polysiloxane b7 having a non-volatile content of 60.0% by mass.

[0148] Next, 350 parts by mass of the polysiloxane b7, 234 parts by mass of phenol, 234 parts by mass of 2-naphthol, 16 parts by mass of melamine, 344 parts by mass of 50% formalin, and 15.4 parts by mass of 25% aqueous ammonia were charged into a reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube, and a nitrogen gas inlet, and the temperature was raised to 80° C. with stirring, and the mixture was reacted at 80° C. for 2 hours. Next, dehydration was performed under reduced pressure of 10 to 300 kPa, and 380 parts by mass of MEK was added to obtain 1,000 parts by mass of a solution of composite resin B9 having a non-volatile content of 60.0% by mass.

[0149] In the obtained composite resin B9, the epoxysilane content was 5 mol %, the phenyltrimethoxysilane content was 90 mol %, and PSi / Ph was 30 / 70.

[0150] [Example 1] (Uniformization process) 640 parts by mass of the silicon nanoparticle dispersion A1 obtained in Synthesis Example 1 and 360 parts by mass of the composite resin B1 produced in Synthesis Example 3 were thoroughly mixed in a stirrer. As a result, a suspension of a negative electrode precursor mixture with a solid concentration of 36.3% by mass was obtained. Next, the solvent was removed in an oil bath at 120°C under nitrogen flow conditions, and then reduced pressure drying was performed at 110°C for 10 hours using a vacuum dryer to obtain a dried product of the precursor mixture as a negative electrode active material precursor.

[0151] (Firing process) The dried product obtained in the homogenization step was fired at 1100° C. for 4 hours in a nitrogen atmosphere to obtain a black solid product.

[0152] (Crushing process) The black solid matter obtained in the above-mentioned firing step was pulverized in a planetary ball mill to prepare a negative electrode active material.

[0153] [Example 2] A negative electrode active material was prepared in the same manner as in Example 1, except that in the homogenization step, 644 parts by mass of the silicon nanoparticle dispersion A1 and 356 parts by mass of the composite resin B2 prepared in Synthesis Example 4 were used to obtain a suspension of a negative electrode precursor mixture having a solid concentration of 36.2 mass%.

[0154] [Example 3] A negative electrode active material was prepared in the same manner as in Example 1, except that in the homogenization step, 587 parts by mass of the silicon nanoparticle dispersion A1 and 413 parts by mass of the composite resin B3 prepared in Synthesis Example 5 were used to obtain a suspension of a negative electrode precursor mixture having a solid concentration of 38.3% by mass.

[0155] [Example 4] A negative electrode active material was prepared in the same manner as in Example 1, except that in the homogenization step, 564 parts by mass of the silicon nanoparticle dispersion A1 and 436 parts by mass of the composite resin B4 prepared in Synthesis Example 6 were used to obtain a suspension of a negative electrode precursor mixture having a solid concentration of 39.1% by mass.

[0156] [Example 5] A negative electrode active material was prepared in the same manner as in Example 1, except that in the homogenization step, 604 parts by mass of the silicon nanoparticle dispersion A2 obtained in Synthesis Example 2 and 396 parts by mass of the composite resin B1 prepared in Synthesis Example 3 were used to obtain a suspension of a negative electrode precursor mixture having a solid concentration of 37.7% by mass.

[0157] [Example 6] A negative electrode active material was prepared in the same manner as in Example 1, except that in the homogenization step, 608 parts by mass of the silicon nanoparticle dispersion A2 obtained in Synthesis Example 2 and 392 parts by mass of the composite resin B2 prepared in Synthesis Example 4 were used to obtain a suspension of a negative electrode precursor mixture having a solid concentration of 37.5 mass%.

[0158] [Example 7] A negative electrode active material was prepared in the same manner as in Example 1, except that in the homogenization step, 550 parts by mass of the silicon nanoparticle dispersion A2 obtained in Synthesis Example 2 and 450 parts by mass of the composite resin B3 prepared in Synthesis Example 5 were used to obtain a suspension of a negative electrode precursor mixture having a solid concentration of 39.7% by mass.

[0159] [Example 8] A negative electrode active material was prepared in the same manner as in Example 1, except that in the homogenization step, 526 parts by mass of the silicon nanoparticle dispersion A2 obtained in Synthesis Example 2 and 474 parts by mass of the composite resin B4 prepared in Synthesis Example 6 were used to obtain a suspension of a negative electrode precursor mixture having a solid concentration of 40.5% by mass.

[0160] [Example 9] A negative electrode active material was prepared in the same manner as in Example 1, except that in the homogenization step, 649 parts by mass of the silicon nanoparticle dispersion A1 obtained in Synthesis Example 1 and 351 parts by mass of the composite resin B5 prepared in Synthesis Example 8 were used to obtain a suspension of a negative electrode precursor mixture having a solid concentration of 36.0% by mass.

[0161] [Example 10] A negative electrode active material was prepared in the same manner as in Example 1, except that in the homogenization step, 667 parts by mass of the silicon nanoparticle dispersion A1 obtained in Synthesis Example 1 and 333 parts by mass of the composite resin B6 prepared in Synthesis Example 9 were used to obtain a suspension of a negative electrode precursor mixture having a solid concentration of 35.3 mass%.

[0162] [Example 11] A negative electrode active material was prepared in the same manner as in Example 1, except that in the homogenization step, 682 parts by mass of the silicon nanoparticle dispersion A1 obtained in Synthesis Example 1 and 318 parts by mass of the composite resin B7 prepared in Synthesis Example 10 were used to obtain a suspension of a negative electrode precursor mixture having a solid concentration of 34.8% by mass.

[0163] [Example 12] A negative electrode active material was prepared in the same manner as in Example 1, except that in the homogenization step, 703 parts by mass of the silicon nanoparticle dispersion A1 obtained in Synthesis Example 1 and 297 parts by mass of the composite resin B8 prepared in Synthesis Example 11 were used to obtain a suspension of a negative electrode precursor mixture having a solid concentration of 34.0 mass%.

[0164] [Example 13] A negative electrode active material was prepared in the same manner as in Example 1, except that in the homogenization step, 709 parts by mass of the silicon nanoparticle dispersion A1 obtained in Synthesis Example 1 and 291 parts by mass of the composite resin 9 prepared in Synthesis Example 12 were used to obtain a suspension of a negative electrode precursor mixture having a solid concentration of 33.8 mass%.

[0165] [Example 14] A negative electrode active material was prepared in the same manner as in Example 1, except that in the homogenization step, 614 parts by mass of the silicon nanoparticle dispersion A2 obtained in Synthesis Example 2 and 386 parts by mass of the composite resin 5 prepared in Synthesis Example 8 were used to obtain a suspension of a negative electrode precursor mixture having a solid concentration of 37.3 mass%.

[0166] [Example 15] A negative electrode active material was prepared in the same manner as in Example 1, except that in the homogenization step, 631 parts by mass of the silicon nanoparticle dispersion A2 obtained in Synthesis Example 2 and 369 parts by mass of the composite resin 6 prepared in Synthesis Example 9 were used to obtain a suspension of a negative electrode precursor mixture having a solid concentration of 36.6 mass%.

[0167] [Example 16] A negative electrode active material was prepared in the same manner as in Example 1, except that in the homogenization step, 648 parts by mass of the silicon nanoparticle dispersion A2 obtained in Synthesis Example 2 and 352 parts by mass of the composite resin 7 prepared in Synthesis Example 10 were used to obtain a suspension of a negative electrode precursor mixture having a solid concentration of 36.0 mass%.

[0168] [Example 17] A negative electrode active material was prepared in the same manner as in Example 1, except that in the homogenization step, 670 parts by mass of the silicon nanoparticle dispersion A2 obtained in Synthesis Example 2 and 330 parts by mass of the composite resin 8 prepared in Synthesis Example 11 were used to obtain a suspension of a negative electrode precursor mixture having a solid concentration of 35.2 mass%.

[0169] [Example 18] A negative electrode active material was prepared in the same manner as in Example 1, except that in the homogenization step, 676 parts by mass of the silicon nanoparticle dispersion A2 obtained in Synthesis Example 2 and 324 parts by mass of the composite resin 9 prepared in Synthesis Example 12 were used to obtain a suspension of a negative electrode precursor mixture having a solid concentration of 35.0 mass%.

[0170] [Comparative Example 1] A negative electrode active material was produced in the same manner as in Example 1, except that in the homogenization step, a suspension of a negative electrode precursor mixture having a solid concentration of 21.9 mass% was obtained using 665.8 parts by mass of the silicon nanoparticle dispersion A1 obtained in Synthesis Example 1, 49.6 parts by mass of the polysiloxane C produced in Synthesis Example 7, and 284.6 parts by mass of a phenolic resin ("HE100C-30" manufactured by Air Water Performance Chemical Inc.) to which methyl ethyl ketone was added as an organic solvent.

[0171] The average particle size (D50) of the silicon nanoparticles was measured using a Mastersizer 3000 (Laser Micron Sizer LMS-3000, manufactured by Malvern Instruments).

[0172] (Measurement of resin decomposition temperature) First, the resin to be measured was dried under reduced pressure at 110°C for 10 hours using a vacuum dryer. The decomposition start temperature of the resin was measured by weighing out about 10 mg of the dried resin into a Pt pan, accurately recording the weight, placing it in a TG-DTA device, and measuring at a heating rate of 10° / min and a maximum temperature of 1000°C under nitrogen flow. The measurement device used was a Rigaku Thermo PIUS EV02. The results obtained were analyzed using software provided with the Rigaku Thermo PIUS EV02, and the decomposition start temperature was recorded.

[0173] (Evaluation of uniformity of dried products) For the dried precursor mixture, carbon, nitrogen, oxygen and silicon were quantified using SEM-EDX (JSM-7800F, manufactured by JEL) to determine the element ratio (mass ratio) C / N / O / Si. For each of Examples 1 to 4 and Comparative Example 1, the results of element mapping of the dried material are shown in Figures 1 to 5, respectively. In Figures 1 to 5, the white mapped areas correspond to silicon (Si) and the black mapped areas correspond to carbon (C).

[0174] (Evaluation of battery characteristics) The negative electrode active material (8 parts by mass), acetylene black (1 part by mass) as a conductive assistant, and organic binder (1 part by mass, breakdown: SBR (0.75 parts by mass) + CMC (0.25 parts by mass)) obtained above were mixed and stirred for 10 minutes with a rotating and revolving type foaming blender to prepare a slurry. The slurry was applied to a copper foil with a thickness of 20 μm using an applicator, and then dried under reduced pressure at 110 °C to obtain a thin electrode film. Next, a circular electrode with a diameter of 14 mm was punched out and pressed using a tablet molding machine so that the thickness was about 40 μm. The thickness was measured by calculating the average value of five points on the thin electrode film using a thickness meter. In a dry room with an extremely low moisture content (dew point -40 °C or less), Li foil was placed opposite the thin electrode film through a polypropylene separator with a thickness of 25 μm. Thereafter, an electrolyte (Kishida Chemical Co., Ltd., 1 mol / L LiPF6, diethyl carbonate:ethylene carbonate = 1:1 (volume ratio)) was adsorbed to prepare a half battery (CR2032 type) for evaluation. The battery characteristics of the obtained half battery were measured using a secondary battery charge / discharge tester (manufactured by Hokuto Denko Corporation). The charge / discharge characteristics (charge / discharge capacity) were evaluated under the set conditions of constant current / constant voltage charge / constant current discharge, with a room temperature of 25°C, a cutoff voltage range of 0.005 to 1.5 V, and a charge / discharge rate of 0.1 C (1 to 3 times) and 0.2 C (after 4 cycles). When switching between each charge / discharge cycle, the battery was left in an open circuit for 30 minutes. The initial efficiency and cycle characteristics (referring to the retention rate of discharge capacity after 10 cycles) were determined as follows. The results are shown in Tables 1 to 4. Initial efficiency (%) = Initial discharge capacity (mAh / g) / Initial charge capacity (mAh / g) Retention rate (%) = initial discharge capacity (mAh / g) / discharge capacity after 10 cycles (mAh / g)

[0175] [Table 1]

[0176] [Table 2]

[0177] [Table 3]

[0178] [Table 4]

[0179] As can be seen from Tables 1 to 4, by using a composite resin of polysiloxane and phenolic resin, the retention rate of discharge capacity could be significantly improved compared to the case where a mixture of polysiloxane and phenolic resin was used. When a composite resin of polysiloxane and phenolic resin was used, as can be seen from a comparison between Figures 1 to 4 and Figure 5, the uniformity of the components in the precursor is higher than that when a mixture of polysiloxane and phenolic resin was used, and therefore such an improvement in the retention rate of discharge capacity is presumably achieved.

Claims

1. Silicon nanoparticles; A composite resin in which a polysiloxane and a phenolic resin are bonded to each other, A composition used to manufacture a negative electrode active material.

2. A method for producing a negative electrode active material, comprising a step of firing a composition containing silicon nanoparticles and a composite resin in which a polysiloxane and a phenolic resin are bonded to each other.

3. A negative electrode active material comprising a fired product of a composition containing silicon nanoparticles and a composite resin in which a polysiloxane and a phenolic resin are bonded to each other.

4. A secondary battery comprising a negative electrode containing the negative electrode active material according to claim 3.

Citation Information

Patent Citations

  • Silicon-based composite negative electrode material for lithium ion battery

    CN104241621A

  • Silicon nanoparticles, non-aqueous secondary battery negative electrode active material using said silicon nanoparticles, and secondary battery

    WO2020129467A1

  • Secondary battery material, negative electrode active material, and secondary battery

    WO2023017694A1

  • Negative electrode active material, method for producing negative electrode active material, and non-aqueous electrolyte secondary battery

    JP7088438B1